ANALISIS KEBERADAAN EMMA LOU DALAM THE BLACKER THE BERRY KARYA WALLACE THURMAN - Asmarani, Ratna (Faculty of Humanities, Diponegoro University, 2016)
This paper deals with the novel entitled The Blacker the Berry written by Wallace Thurman. The focus of analysis is on the existence of Emma Lou, a young woman with very black skin. The literary research method used is the contextual method supported by Sartre’s ‘Modes of Existence’, Bergoffen’s concept on female’s body, the concept of intra-racial racism, and Faludi’s ‘Backlash’ framed in feminist literary criticism. The result shows that it is not easy for a young, black-skinned woman to live in a world still strictly applied intra-racial racism. She has to endure a bombardment of existential backlashes in the form of otherness due to the ideology adoring lighter skin. Her decision to construct her own existence emerges after she is able to accept her specific blackness.